On Newton-Kantorovich Method for Solving the Nonlinear Operator Equation - Hameed Husam Hameed; Z. K. Eshkuvatov; Anvarjon Ahmedov; N. M. A. Nik Long (Abstract and Applied Analysis)
We develop the Newton-Kantorovich method to solve the system of 2×2 nonlinear Volterra integral equations where the unknown function is in logarithmic form. A new majorant function is introduced which leads to the increment of the convergence interval. The existence and uniqueness of approximate solution are proved and a numerical example is provided to show the validation of the method.